Tourısm Management Strategy In The Natural Tourısm Park Area Of Buyan Lake And Tamblıngan Lake, Balı - Made Sera Septiani; I Nyoman Sunarta; Syamsul Alam Paturusi (Cita Konsultindo Research Center, 2024)
Management remains a challenge for many tourism destinations, including the Lake Buyan and Lake Tamblingan areas, which have complex tourism management issues. Lake Buyan, outside the conservation area, still lacks clear tourism management, while the management of Lake Tamblingan, particularly within the conservation area, opens opportunities for natural resource extraction. Management in these areas has not yet been optimal in terms of conservation efforts, tourism activities, and sustainability aspects. This research aims to structure management through tourism management strategies to provide benefits and fairness to the stakeholders involved, as well as efforts to improve performance and effectiveness, especially management capacity.This research examines the phases of tourism development, current management conditions, as well as internal and external factors. Data for this research were obtained through observation and in-depth interviews. The data were analyzed using qualitative data analysis techniques with NVivo and further analyzed using SWOT analysis to find tourism management strategies in the Lake Buyan and Lake Tamblingan Nature Tourism Park areas.The research results show that Lake Buyan is in the development phase, and Lake Tamblingan is in the involvement phase. Tourism management in the Lake Buyan and Lake Tamblingan Nature Tourism Park is in a balanced internal-external condition, with 8 strength factors, 6 weakness factors, 5 opportunity factors, and 5 threat factors. Based on internal and external conditions, the combination of SO, WO, ST, and WT strategies are compiled as follows: zoning of utilization areas, digital promotion, human resource development, stakeholder collaboration, transparency of retribution results, enhancement of nature-loving programs for tourists, organization of events highlighting tourism potential, and disaster management planning.